(untitled) (Research, Society and Development, 2020)
The objective was to quantify the affirmative actions at the Federal University of Goiás, Regional Jataí (UFG-REJ), between 2010 and 2018, based on the number of new entrants. A retrospective and census study of data related to undergraduate courses was carried out through descriptive analysis and the investigation was developed from documentary, bibliographic and empirical research using the data available at the Undergraduate Coordination including measures for monitoring and permanence of students. The data were organized using the Microsoft® Excel 2013 program, version for Windows 10, which allowed the assembly of tables and graphs by grouping the information by year, and by special academic unit, students with disabilities, type of disability, self-declared brown and indigenous blacks, family income and from public schools. In 2010, 25.16% of those enrolled enrolled at UFGInclui the quota for students from public schools, while in 2018, 34.39% enrolled through quotas. In the same period, of the total of 5,700 students enrolled, 0.62% declared special needs. In conclusion, the history of affirmative actions at UFG-REJ proved to be reasonable and proportional to that practiced in Brazilian territory. However, financial and pedagogical actions are still needed. The analysis carried out in this study will be essential for the design of future actions at UFJ since it is necessary to contextualize the history of these students and to know the profile of the freshmen allowing not only their admission, but their permanence in the institution.